Guidelines of the Russian gastroenterological association on diagnostics and treatment of a chronic pancreatitis - V. T. Ivashkin; I. V. Mayev; A. V. Okhlobystin; Yu. A. Kucheryavyy; A. S. Trukhmanov; A. A. Sheptulin; O. S. Shifrin; T. L. Lapina; M. F. Osipenko; V. I. Simanenkov; I. B. Khlynov; S. A. Alekseyenko; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.